The Global Role of Cities Government on Tackling Covid-19 - Dyah Estu Kurniawati; Eko Priyo Purnomo; Ali Roziqin; Rizka Zahrotun Khairina (Journal of Government and Civil Society, 2022)
Decentralization have encouraged substate actors to take the opportunity to conduct international relations and cooperation in an effort to combat the negative impacts of Covid-19. The method of this study is a literature review of 20 journal articles from Google Scholar and ResearchGate with paradiplomacy, the global role of cities, and the handling of covid-19 as keywords. The study also used sources from credible news websites. Data analysis using MAXQDA with coding methods. The codes are classified based on the categories of journals and articles that have been collected. As a result, the world’s city governments have some aggressive responses to combat Covid-19. The responses are cooperation through sister city schemes, global city networks, partnerships with NGOs, partnerships with IGO, seeks to promote dialogue in diplomatic tensions, partnerships with foreign military forces and conducting foreign missions. The current article aims to support future research in this growing field by highlighting some of the most important findings, questions, and approaches, focusing on how paradiplomacy creates a pattern of communication between cities, especially during difficult times such as a pandemic. Studi ini menggambarkan bagaimana peran global pemerintah kota dalam menanggulangi Covid-19 dengan paradiplomacy. Globalisasi dan Desentralisasi telah mendorong para pelaku substate untuk mengambil kesempatan melakukan hubungan dan kerja sama internasional dalam upaya untuk memerangi dampak negatif Covid-19. Metode dari penelitian ini adalah tinjauan literatur dari 20 artikel jurnal dari Google Scholar dan ResearchGate dengan kata kunci paradiplomasi, peran global kota, dan penanganan covid-19. Studi ini juga menggunakan sumber-sumber dari situs web berita yang kredibel. Analisis data menggunakan MAXQDA dengan metode coding. Kode-kode tersebut diklasifikasikan berdasarkan kategori dari jurnal dan artikel yang telah dikumpulkan. Hasilnya, pemerintah kota di dunia memiliki beberapa respons agresif untuk memerangi Covid-19. Respon tersebut antara adalah kerjasama melalui skema sister city, jaringan kota global, kemitraan dengan LSM, kemitraan dengan IGO, berusaha untuk mempromosikan dialog dalam ketegangan diplomatik, kemitraan dengan pasukan militer asing dan melakukan misi asing.